The Use of Information Technology and Hospital Information Systems: A Study on Health Employees - Işık, Oğuz; Akbolat, Mahmut (Information World, 2010)
The aim of this study is to demonstrate the skills of using information technologies and hospital information systems of health employees and to evaluate their ideas about benefits of hospital information systems. Study was implemented in 11 hospitals operating in Sakarya on April 2009. 544 health employees have participated in the research. Data were collected by questionnaires. Descriptive statistical methods, independent sample t test and One Way ANOVA test were used to analyze the data. Reliability of the survey was calculated by using of Cronbach’s alpha coefficient. Results were assessed in a 95% confidence interval, p <0.05 significance level. According to results of the study, health employees think that they are more proficient in Office programs, operating systems, computer hardware, and the use of hospital information systems. Also, health employees think that to use information technology in their departments is important. They can use modules of hospital information systems more in their own departments. According to health employees, hospital information systems were mostly used to access information easily, provide better quality medical services, prevent time loss, facilitate communication between employees, give an appointment to outpatients to assign the patients.